Contextual Influences: Building Brand Community in Large and Small Colleges - McAlexander,Jim; Koenig,Hal (Journal of Marketing for Higher Education, 2010)
This research extends recent efforts that have introduced and empirically tested a conceptual model of brand community in the context of higher education. This emerging literature has indicated that brand community provides a framework that can inform and guide marketing investments in ways that lead to affinity and stronger loyalty to the brand and institution. This paper presents the results of a national survey that examines the potential impact that institutional size may have on the relationships of an alumni brand community. This paper also explores the implications of the size of the educational institution on relevant and desired marketing outcomes that include the willingness to recommend the university to friends and family and a desire to purchase licensed apparel
Keywords: Marketing